Terretêktorh: space and timbre, timbre and space - Santana, Helena (2012)
In this article, we will analyze the way in which Xenakis uses space, fills it with sound and colors it according to the processes of composition used in his work Terretêktorh. Does there exit a particular way of spatializing the timbre in Xenakis and in particular, in this work? Do there exist rhythms of timbre? We will try to understand and answer these questions in the course of this study. Terretêktorh has been selected because it is a very rich work in this domain. Even in the placement of the players, Xenakis reveals a vast undertaking: he granulates the entire orchestra over a circular space with the percussion on the periphery of the instrumental circle to enclose the sounds.